Nitrogen-doped carbon derived from pre-oxidized pitch for surface dominated potassium-ion storage. (December 2019) - Sun, Qing; Li, Deping; Cheng, Jun; Dai, Linna; Guo, Jianguang; Liang, Zhen; Ci, Lijie
Abstract: Graphitic material has captured tremendous attentions as anode material for potassium ion batteries (PIBs). Nevertheless, the large radius of potassium-ions results in sluggish potassiation kinetics and huge volume expansion, leading to unsatisfying performance. Herein, a fabrication facile, cost-effective and high carbon yield nitrogen/oxygen co-doped amorphous carbon (NOC) with pitch and urea as precursors is reported. Pre-oxidation process is employed, maintaining the amorphous structure of pitch derived carbon against its soft carbon nature. The NOC electrode delivers reversible capacities of 347 (300th cycle) and 167 mAh g −1 (1000th cycle) at 100 and 2000 mA g −1, respectively. Rearrangement of graphene layers in short range benefits the structure stability against volume change. Kinetics analyses prove that surface-induced capacitive process dominates in K-ion storage mechanism, which contributes to the remarkable electrochemical performance. Pouch full cells were assembled, delivering a capacity of 316 mAh g −1 at 100 mA g −1 . In view of the cost-effectiveness and electrochemical performance, this work offers a strategy for the fabrication of low-cost and high-performance PIB anode materials. Graphical abstract: The nitrogen-doped carbon is synthesized with precursors of pitch and urea. Pre-oxidation process is employed to induce oxygen-containing functional groups, avoiding the melting or reordering of pitch molecules during carbonization against its soft carbon nature. Benefiting from the amorphous structure, the NOC electrodes present surface-dominated storage behavior, exhibiting advantages of low-cost and high-performance. Image 1